Direct printing of metal oxide nanostructures for wearable electrochemical sensing - Nithin Krisshna Gunasekaran; Harikrishnan Muraleedharan Jalajamony; Santhosh Adhinarayanan; Soumadeep De; Reven Adu; Shawn Strobel; Govindarajan T Ramesh; Renny Edwin Fernandez (Scientific Reports)
Abstract Metal oxides such as Zinc Oxide (ZnO) and Cerium Oxide (CeO2) have emerged as promising materials for electrochemical sensing due to their redox activity, surface charge sensitivity, and chemical stability. We report the direct printing of ZnO and CeO2 nanostructures on flexible screen-printed electrodes using an atmospheric plasma-aided technique, enabling binder-free printing from aqueous suspensions. The electrochemical sensing ability of ZnO was tested for pH sensing, while CeO2 was tested for non-enzymatic Hydrogen Peroxide (H2O2) detection. Morphological and optical characterizations revealed voltage-dependent variations in nanoparticle distribution, thickness, and bandgap, with improved layer uniformity and substrate adhesion at higher plasma voltages. Electrochemical characterization demonstrated enhanced charge transfer and sensitivity, with ZnO showing a maximum pH response of 34.96 mV/pH when fabricated at 18 kV and CeO2 reaching a peak H2O2 sensitivity of 1.03 µA/µM/cm² when fabricated at 24 kV. Our results establish plasma-assisted printing as a binder free, rapid, low-temperature method for directly printing high-performance metal oxide sensors on flexible polymer substrates for wearable applications.